Occurrence and Molecular Characterization of Some Parasitic Copepods (Siphonostomatoida: Pandaridae) on Pelagic Sharks in the Mediterranean Sea - Palomba, Marialetizia; Insacco, Gianni; Zava, Bruno; Santoro, Mario (Frontiers in Marine Science, 2022)
Copepods of the family Pandaridae are typically ectoparasites of elasmobranch fishes. They display a cosmopolitan distribution and limited host specificity. Published literature on their occurrence on pelagic sharks in the Mediterranean is scarce, often from the past century, or scattered through fish parasite surveys. Moreover, of the 64 valid pandarid species known at present, molecular data from GenBank exists for only 10 species and there are no data from the Mediterranean. In this study, we begin addressing this knowledge gap by exploring the molecular features of some pandarid copepods (i.e., Dinemoura latifolia, Echthrogaleus coleoptratus, Pandarus satyrus, and Phyllothyreus cornutus) and their phylogenetic relationships using new material from pelagic sharks (i.e., Prionace glauca, Isurus oxyrinchus, and Carcharodon carcharias) in the Mediterranean. Genetic distances analysis showed intraspecific variation in the mitochondrial DNA cytochrome oxidase c subunit 1 (mtDNA cox1) sequences and interspecific variations of 0.001-0.081 and 0.196-0.288, respectively for the small subunit ribosomal DNA (SSU rDNA) and the cox1 gene locus. Phylogenetic analyses of pandarid copepods based on sequences available in GenBank plus the sequences generated by our study revealed two major clades: the first, with strong nodal support, included species of Pandarus, Phyllothyreus, Pannosus and Pseudopandarus; the second, with weaker nodal support, included species of Achtheinus, Perissopus, Echtrogaleus, Nesippus, and Dinemoura. As most pandarid species are missing from the present analyses, we discuss the limitations of our phylogenetic results. Nevertheless, this study represents a first step towards to yielding new information about the phylogeny of parasitic copepods on pelagic sharks in the Mediterranean.